Cultural Policy of Russia and Hungary: Modern Discourse and New Actors - Szűcs, Olga; Yudina, Tatyana (Slavica, 2018)
The authors of the article argue that contemporary cultural policy discourse is in the focus of attention of scientific communities, social and political organizations and government institutions. It represents a sort of symbolic struggle and nominations and has necessitated a new approach to cultural policy structuring. The article shows that this necessity is demonstrated by the development of cooperation between Russia and Hungary in terms of cultural sectors and cultural heritage. Expert communities and non-governmental organizations are becoming significant elements in the structure of cultural policy subjects. The association “For Hungarian-Russian cooperation named after Leo Tolstoy” has become such a key issue. The authors of this article attempt to highlight the most essential contemporary issues in the sphere of cultural policy in general and in relation of two separate countries – Russia and Hungary – through the scientific project “Hygiene of culture”.